IMPLEMENTASI KHIYAR DALAM JUAL BELI ONLINE: STUDI KASUS KETIDAKSESUAIAN OBJEK PADA MARKETPLACE SHOPEE - Syathir Sofyan; Teti (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
The purpose of the research is to find out how to implement the khiyar principle in online buying and selling, case studies of object inconsistencies in the Shopee marketplace and to find out the inhibiting factors for khiyar implementation in online buying and selling case studies of object mismatches. The type of research used in this study is a qualitative descriptive method. Data collection techniques consist of interviews and documentation. The data obtained will be analyzed in three steps, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of khiyar in online buying and selling in cases of object mismatch in practice has implemented khiyar, although in terms of knowledge and literacy about khiyar both from Shopee, sellers, and buyers do not fully understand about khiyar. On the Shopee marketplace site, the khiyar practices applied are “khiyar aib”, “khiyar syarat”, and “khiyar ru’yah”. Khiyar aib is related to the right of complaint owned by the buyer when receiving a defective item. Khiyar syarat relate to the grace period given by the Shopee to the buyer to make a complaint. And for khiyar ru’yah it relates to the right of complaint owned by the buyer because he cannot see the goods ordered directly when the contract takes place.